Susceptibility testing of infectious agents and evaluation of performance of antimicrobial susceptibility test devices. Broth micro-dilution reference method for testing the in vitro activity of antimicrobial agents against rapidly growing aerobic bacteria involved in infectious diseases Part 1, (7th July 2020) - British Standards Institution,
No abstract available